The Psychometric Properties of the Norwegian version of Multidimensional Anxiety scale for children (MASC) - Villabø, Marianne; Neumer, Simon-Peter (PsykTestBarn, 2017)
Description: Multidimensional Anxiety Scale for Children (MASC) assesses symptoms of anxiety in children and adolescents. American norms exist for ages 8–17 years. The MASC was developed by John March and colleagues in 1997, and Multi-Health Systems currently hold the distributing rights to the scale. The MASC consists of 39 items which make up four subscales. The scale is a self-report measure completed by the young person. More recently, the MASC has been adapted for parent report as well. Literature search: The systematic literature search resulted in 12 Norwegian and 30 Swedish or Danish publications. Five Norwegian and two Swedish publications were included in the present review. Three of the five Norwegian publications presented data from the same study. The Norwegian studies presented data from three clinical samples from treatment-seeking patients aged 7–13 years. Psychometrics: Norwegian norms are not available, but American norms may be applied. Swedish norms exist for adolescents. Studies found good to excellent internal consistency, but low agreement between child- and parent-report. The total score distinguished between children with and without an anxiety disorders, and the subscales for social anxiety and separation/panic predicted the presence of social phobia and separation anxiety disorder respectively, supporting the construct validity of the scale. Conclusion: The Norwegian translation of the MASC has demonstrated good psychometric properties in line with international studies.